Sodium Storage and Electrode Dynamics of Tin–Carbon Composite Electrodes from Bulk Precursors for Sodium‐Ion Batteries. (11th March 2019) - Palaniselvam, Thangavelu; Goktas, Mustafa; Anothumakkool, Bihag; Sun, Ya‐Nan; Schmuch, Richard; Zhao, Li; Han, Bao‐Hang; Winter, Martin; Adelhelm, Philipp
Abstract: Here, a Sn–C composite material prepared from bulk precursors (tin metal, graphite, and melamine) using ball milling and annealing is reported. The composite (58 wt% Sn and 42 wt% N‐doped carbon) shows a capacity up to 445 mAh gSn+C −1 and an excellent cycle life (1000 cycles). For the graphite, the ball milling leads to graphene nanoplatelets (GnP) for which the storage mechanism changes from solvent co‐intercalation to conventional intercalation. The final composite (Sn at nitrogen‐doped graphite nanoplatelets (SnNGnP)) is obtained by combining the GnPs with Sn and melamine as the nitrogen source. Rate‐dependent measurements and in situ X‐ray diffraction are used to study the asymmetric storage behavior of Sn, which shows a more sloping potential profile during sodiation and more defined steps during desodiation. The disappearance of two redox plateaus during desodiation is linked to the preceding sodiation current density (memory effect). The asymmetric behavior is also found by in situ electrochemical dilatometry. This method also shows that the effective electrode expansion during sodiation is much smaller (about +14%) compared to what is expected from Sn (+420%), which gives a reasonable explanation for the excellent cycle life for the SnNGnP (and likely other nanocomposites in general). Next to the advantages, challenges, which result from the nanocomposite approach, are also discussed. Abstract : Tin supported by nitrogen‐doped graphene nanoplatelets is found to be an efficient anode for sodium‐ion batteries. Rate‐dependent measurements and in situ diffraction reveal the asymmetric storage behavior of tin within a cycle as well as a memory effect. The in situ electrochemical dilatometry study shows the active role of the support in mitigating the large volume changes of tin during (de)sodiation.